Angela Grauerholz et ses livres - Tougas, Colette (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract In this essay, the author stresses two characteristics of Angela Grauerholz's photographic corpus: the fortuitous and the systematic. The author highlights the important role played by desire on the part of the receiver. She then observes how these same aspects are embodied in the twelve books that Grauerholz has produced from her collections of images and texts as part of the project Reading Room for the Working Artist Bringing together writings and works around sometimes unusual themes, these open encyclopedias appeal to each reader's personal imagination and cultural memory.